Effect of dipping and dusting on quality of fried chicken during storage - Kyaw, Ei Mon Mon; Therdthai, Nantawan; Jagnchud, Kamolwan; Jangchud, Anuvat (Food and Applied Bioscience Journal, 2017)
Fried foods are very common and generally consumed worldwide. In the fried chicken, batter coating plays an important role on product quality. This study aimed to determine effect of dipping and dusting on quality of the fried chicken during storage at 50°C for 3 h. Prior to frying at 170°C, the reformed chicken meat was subjected to 4 conditions including 1) dipping in batter with 0% Hydroxypropyl methylcellulose (HPMC), 2) dipping in batter with 2% HPMC, 3) dipping in batter with 0% HPMC and dusting with wheat flour and 4) dipping in batter with 2% HPMC and dusting with wheat flour. By further dusting after dipping in batter with HPMC could maintain crispness of the fried chicken storage at 50°C for 3 h. From the triangle test, dusting could maintain crispness of the fried chicken for 3 h without significant difference between freshly fried chicken and 3 h-storage fried chicken. Moreover, the moisture content of the fried chicken crust from dipping in the batter with 2% HPMC and dusting was remained at the lowest during storage. Therefore, the optimum condition was that chicken should be dipped in the batter containing 2% HPMC and dusting in the wheat flour before frying at 170°C.